2020
DOI: 10.1108/mhrj-09-2019-0033
|View full text |Cite
|
Sign up to set email alerts
|

Public awareness of psychological problems in Pakistan

Abstract: Purpose Awareness of psychological problems is essential to address the problems adequately. It also contributes positively in the overall psychosocial well-being of a society. The rates of mental health literacy have been investigated in many countries and have been found to be lower than expected. The purpose of this study was to explore public awareness of psychological problems and psychological treatment in Pakistan. Design/methodology/approach The current study explored the latest levels of public awar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…They are condemned for being infertile (Husain & Imran, 2020) and humiliated for being a matter of shame for the family (Gill, 2010). These situations put women at a higher risk of several psychological problems (Husain, 2018;Husain & Faize, 2020;Husain & Qureshi, 2016), which stay unresolved (Husain, 2019). The negativity in the attitudes towards women is based on several psychosocial factors such as gender (Wendt & Shafer, 2016), age (Twenge, 1997a), mental health (Parry, 1987), anxiety (Wade & Gelso, 1998), depression (Halloran, 1998), self-esteem (McCall & Struthers, 1994;Napholz, 1995;Pryor, 1994;Shimonaka et al, 1997;Wilhelm et al, 1997), locus of control (Furnham & Gunter, 1988), organizational requirements (García-Retamero & López-Zafra, 2006), political orientation (Whitley & Egisdóttir, 2000), religion (Emerson & Hartman, 2006), racism (Cragun & Sumerau, 2015) and culture (Costa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…They are condemned for being infertile (Husain & Imran, 2020) and humiliated for being a matter of shame for the family (Gill, 2010). These situations put women at a higher risk of several psychological problems (Husain, 2018;Husain & Faize, 2020;Husain & Qureshi, 2016), which stay unresolved (Husain, 2019). The negativity in the attitudes towards women is based on several psychosocial factors such as gender (Wendt & Shafer, 2016), age (Twenge, 1997a), mental health (Parry, 1987), anxiety (Wade & Gelso, 1998), depression (Halloran, 1998), self-esteem (McCall & Struthers, 1994;Napholz, 1995;Pryor, 1994;Shimonaka et al, 1997;Wilhelm et al, 1997), locus of control (Furnham & Gunter, 1988), organizational requirements (García-Retamero & López-Zafra, 2006), political orientation (Whitley & Egisdóttir, 2000), religion (Emerson & Hartman, 2006), racism (Cragun & Sumerau, 2015) and culture (Costa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…They are condemned for being infertile (Husain and Imran, 2020) and humiliated for being a matter of shame for the family. These situations put women at a higher risk of several psychological problems (Husain, 2018; Husain and Qureshi, 2016; Husain and Faize, 2020), which stay unresolved (Husain, 2019). The findings of the current study serve as a fresh air for women by projecting higher levels of psychosocial health among them as compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…Noticeably, the overall psychosocial wellbeing of Pakistanis is also not up to the mark. They do face several psychosocial stressors in their day-to-day routine , suffer from several mental problems (Husain, 2018), lack proper information on mental health (Husain & Faize, 2020), and avoid psychotherapeutic consultation (Husain, 2020). An earlier study revealed that medical doctors and nurses in Pakistan, who are supposed to enhance the health of their countrymen, had alarming levels of depression, anxiety, and stress themselves, compared with other professions (Hassan & Husain, 2020).…”
Section: Discussionmentioning
confidence: 99%